THE IMPACT OF FINANCIAL DETERMINANTS ON MALAYSIAN REITS’ PERFORMANCE (Journal of Business Management and Accounting, 2023)
Property investment in Malaysia has experienced tremendous growth and is considered one of the prime investments by investors due to its stable return growth over the years. This study examined the effects of six financial determinants (earnings per share, debts to assets, price- to-book value, dividend yield, market capitalisation, and return on equity) on the annual return of Malaysian Real Estate Investment Trusts (REITs). The common performance indicator of company can be seen in the percentage change in stock price plus when the dividend paid at the end of the year is used to measure the annual return performance of REITs. A total of 154 firm year observations for a sample of 14 Malaysian REIT companies were examined for a period of 11 years (2008-2018) from the Bloomberg terminal. Multiple regression analysis was used to analyse the data. Findings showed that there is a positive relationship between earning per share, price-to-book value and dividend yield and REITs’ annual return. On the other hand, this study showed that there is no significant relationship between debts to assets and REITs’ annual return. The results also showed that market capitalisation and return on equity are negatively related to Malaysian REITs’ annual returns. Overall, the results highlighted two key features. First, earnings per share and return on equity should be used by investors and management to assess the profitability and operational efficiency of REITS. Second, the investors should use dividend yield as one of the key investment criteria when assessing REIT investment decisions. This study contributed to the literature in REITs by increasing the effects of the explanatory power of financial determinants on REITs’ annual returns.